FOURNIER’S GANGRENE: OUR EXPERIENCE AT A TERTIARY CARE HOSPITAL - Rashid Aslam1 , Muhammad Alam2 , Nadir Shah3, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: An unusual, rapidly spreading fulminant form of necrotizing fasciitis that can spread to the abdominal wall in the space between the fascial planes and affects the vaginal, perianal, and perineal regions called Fournier's gangrene. OBJECTIVE: The goal of this study is to describe, analyse, and discuss the epidemiological, clinical, therapeutic, and evolutionary aspects of Fournier's gangrene. MATERIALS AND METHODS: This retrospective case series was carried out at General Surgery Department of Hayatabad Medical Complex Peshawar from January 2020 to June 2022. Analysis was done on the primary causes, risk factors, postoperative complications outcomes, and long-term follow-up findings. RESULTS: Total 46 patients were included in the study. Age ranged between 20-70 years with a mean age of 45 years. There were 36(78.2%) males and 10(21.7%) females with a male to female ratio of 3.6:1. Diabetes mellitus was found to be the most common risk factor 16(34.8%) followed by Tobacco 11(23.9%), Alcohol 8(17.4%), rectal adenocarcinoma 5(10.8%), morbid obesity 3(6.5%) & paraplegia 3(6.5%). Etiology was found in 31(67%) cases which includes, 13(28.2%) due to anal abscess; 7(15.2%) had a hemorrhoidal pathology, 5 (10.8%) anal fissure, 3(6.5%) had anal fistula and 3(6.5%) haddeveloped the disease following perineal trauma. CONCLUSION: Fournier's Gangrene is a medical and surgical emergency with a high mortality and morbidity rate. Patients are saved through early diagnosis, antibiotic treatment, and high-quality debridement.